From Control Loss to Autonomous Operation: Failsafe Strategies for Modern UAVs - Khrystyuk, Andriy; Cherniuk, Oleksandr (Моделювання, керування та інформаційні технології, 2025)
This paper analyzes the operating principles of the ExpressLRS radio control system for unmanned aerial vehicles (UAVs). It examines mechanisms for protecting UAVs from loss in the event of signal loss and explores various UAV behavior options in such situations. The study identifies possible ways to implement UAV protection mechanisms and highlights the potential for the UAV to perform a specific task even after radio communication with the operator is lost